Acceptability of goat's milk in high and elementary school networks (Acta Scientiarum. Animal Sciences, 2020)
The goat's milk is an excellent choice to replace cow’s milk for children and adults, who are allergic to cow’s milk. Both the proteins and the fat portion of goat’s milk are absorbed by the body faster than cow's milk. Visually it is not possible to differentiate cow’s milk from goat’s milk, which can be differentiated through odor and taste which generates some concern to consumers. The objective of this study were to evaluate the acceptability of goat’s milk, compared to cow’s milk by children and young adults between 06 and 21 years old, in public network of schools Bambuí–MG, living in different socioeconomic levels, in order to verify if there is difference, in acceptance, between these two types of milk and study if the age and socioeconomic status could influence the results. Samples were prepared with chocolate powder and subjected to sensory evaluation by a group of 330 students, who are milk consumers. The samples were evaluated for preference through the hedonic scale of 5 points, asking about the score of the consumers and the preference of each type of milk. The test was conducted in two public schools.  the data were submitted to ANOVA and Tukey test for comparison of means. Although goat's milk has some compositional characteristics and different physicochemical properties of cow's milk, there was no difference between them, due to acceptability between students of the public high school and elementary school network. The mixture 50% goat milk + 50% cow's milk generated greater rejection of the sampled population, a fact justified by the formation of small clots when mixing the different types of milks. Conventional cow's milk can be replaced by goat's milk in school meals, regardless of the age group and socioeconomic status of students.